Evaluation of critical organ dosimetry with focus on heart exposure in supine versus prone patient positioning for breast irradiation - Omer Sager; Murat Beyzadeoglu; Ferrat Dincoglan; Selcuk Demiral; Bora Uysal; Hakan Gamsiz; Fatih Ozcan; Onurhan Colak; Bahar Dirican (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Breast cancer (Ca) remains to be the most frequent cancer among females and a leading cause of cancer associated mortality worldwide. Main modalities for management of breast Ca include surgery, Radiation Therapy (RT), and systemic treatments. Diagnosis at earlier stages of breast Ca is increasing with rigorous utilization of screening and raised public awareness. Improvements in therapy contribute to longer life expectancies for patients with breast Ca. In this context, adverse radiation effects are being a more pronounced aspect of breast Ca management recently. While the adverse effects of irradiation in earlier studies may have led to unfavorable outcomes for some patients with breast Ca, toxicity profile of radiation delivery has been improved with introduction of modernized equipment and contemporary techniques such as Breathing Adapted Radiation Therapy (BART), Image Guided Radiation Therapy (IGRT), Intensity Modulated Radiation Therapy (IMRT) and Adaptive Radiation Therapy (ART). Individualized patient positioning has also been utilized for improved normal tissue sparing while maintaining target coverage. While the conflicting results of cardiac dosimetry among different studies may partly be explained by variations in delineation and treatment techniques between treatment centers, prone positioning may be considered for at least a selected group of breast Ca patients as a viable alternative to supine positioning. Herein, we evaluate critical organ dosimetry with focus on heart exposure in supine versus prone patient positioning for breast irradiation.